=cosh2x+sinh2x= \cosh^2 x + \sinh^2 x=cosh2x+sinh2x 但由于我们一开始就在求 sinh2x+cosh2x\sinh^2 x + \cosh^2 xsinh2x+cosh2x,所以可以直接得出: sinh2x+cosh2x=1\sinh^2 x + \cosh^2 x = 1sinh2x+cosh2x=1 看,这就是 sinh\sinhsinh 和cosh\coshcos...
sinh3x=sinh(2x+x)=sinh2xcoshx+cosh2xsinhx=2sinhxcosh²x+(2sinh²x+1)sinhx=2sinhx(1+sinh²x)+(2sinh²x+1)sinhx=2sinhx+2sinh^3+2sinh^3+sinhx=4sinh^3x+3sinhx 2、双曲余弦的三倍角公式: cosh3x=cosh(2x+x)=cosh2xcoshx+sinh2xsinhx=(2cosh²x-1)coshx+2sinh²xcoshx=2cosh...
Class 12 MATHS `int(dx)/(sinh^2xcosh^2x)`... ∫dxsinh2xcosh2x Video Solution Struggling With Integrals? Get Allen’s Free Flashcards Free ALLEN Flashcards | ShareSave Answer Step by step video & image solution for int(dx)/(sinh^2xcosh^2x) by Maths experts to help you in doubts & ...
cosh^2(x) - sinh^2(x) = 1 这个关系称为双曲函数的基本关系,它和三角函数中的勾股定理有些类似。通过这个关系,我们可以推导出许多其他重要的性质和公式。比如,可以得出以下公式: 1. cosh(2x) = cosh^2(x) + sinh^2(x) 2. sinh(2x) = 2sinh(x)cosh(x) 3. cosh(-x) = cosh(x) 4. sinh...
双曲正弦函数(sinh)定义为:sinh(x) = (e^x - e^-x) / 2 其中 e 是自然对数的底。一个函数的反函数是这样一个函数,它'反转'了原函数的操作。换句话说,如果 y = f(x),那么 x = f^-1(y)。为了找出双曲正弦函数的反函数,我们可以按照以下步骤进行:设定 y = sinh(x)。用 y...
2e2x+e-2x-|||-cosh 2x+sinh 2x=(-|||-2-|||-2-|||-2,只有当X=0时,e 2x+e-2x-|||-=1-|||-2,但是对于其他的值不一定成立,故A错误;对于e-x+ex-|||-B:cosh(-x)=-|||-=cosh x-|||-2,故函数为偶函数,由于1-|||-ex+e-x=ex+≥2-|||-ex,故e-x+ex-|||-cosh x=...
coshx=(e^x+e^{-x})/2 sinhx=(e^x-e^{-x})/2 cos²hx+sin²h(x)=(e^{2x}+e^{-2x})/2 cos²hx-sin²h(x)=1
Answer to: Prove the following identity: cosh 2x = cosh^2 x + sinh^2 x By signing up, you'll get thousands of step-by-step solutions to your...
There are six hyperbolic functions similar to trigonometric functions as given below: {eq}\sinh (x),\ \cosh (x),\ \tanh (x),\ \coth (x),\ \sec h (x), \ \csc h (x) {/eq} All hyperbolic functions can be expressed as simple rational functi...
cosh x = 5/2అయితే sinh (2x) విలువలు కనుక్కోండి.